The critical importance of pharyngeal contractile forces on the validity of intrabolus pressure as a predictor of impaired pharyngo‐esophageal junction compliance. Issue 10 (24th May 2018) - Szczesniak, M. M.; Wu, P. I.; Maclean, J.; Omari, T. I.; Cook, I. J.
Abstract: Introduction: Restrictive defects of the pharyngo‐esophageal junction (PEJ) are common in both structural and neurological disorders and are amenable to therapies aiming to reduce outflow resistance. Intrabolus pressure (IBP) acquired with high‐resolution manometry and impedance (HRMI) is an indicator of resistance and a marker of reduced PEJ compliance. Constraints and limitations of IBP as well as the optimal IBP parameter remain undefined. Aims: To determine: (i) the impact of peak pharyngeal pressure (PeakP) on the diagnostic accuracy of IBP for the detection of a restrictive defect at the PEJ and (ii) the optimal IBP parameter for this purpose. Methods: In 52 dysphagic patients previously treated for head and neck cancer. Five candidate IBP measures and PeakP were obtained with HRMI, as well as a presence of a stricture determined by a mucosal tear after endoscopic dilatation. Predictive values of IBP measures were evaluated by receiver operating characteristic (ROC) analysis for all patients and reiterated as patients with lowest PeakP were progressively removed from the cohort. Results: All IBP parameters had fair to good accuracy at predicting strictures. Intrabolus pressure measured at a discrete point of maximum admittance 1 cm above the maximal excursion of the upper esophageal sphincter had highest sensitivity (0.76) and specificity (0.78). When PeakP was at least 57 mm Hg both sensitivity and specificity improved to 0.9. Conclusions: Pharyngeal propulsive force has substantial impact on the accuracy of IBP as a predictor of a PEJ stricture. When PeakP is ≥57 mm Hg, an elevated IBP is highly predictive of a restrictive defect at the PEJ. Abstract : Intrabolus pressure acquired with high‐resolution manometry and impedance is an indicator of resistance and a marker of reduced pharyngo‐esophageal junction compliance. Pharyngeal propulsive force has substantial impact on the accuracy of IBP as a predictor of a pharyngo‐esophageal junction stricture.